Method for recycling rare earth element yttrium from waste fluorescent powder and preparing resin surface composite coating - WANG HUAIDONG; WU YUFENG; TAN ZHE; CHEN XI (2016)
The invention discloses a method for recycling rare earth element yttrium from waste fluorescent powder and preparing a resin surface composite coating, and belongs to the field of solid waste resource utilization. The method comprises the following steps of: mechanically crushing a waste CRT fluorescent screen and screening the crushed waste CRT fluorescent screen through a screen with certain mesh number to remove impurities such as glass, thereby obtaining fluorescent powder oriented powder; carrying out oxidizing and acid-leaching treatment on the screened fluorescent powder, and leaching out rare earth elements in the fluorescent powder; extracting most of yttrium and a small part of europium through a multi-stage extracting method, reversely extracting to obtain a yttrium chloride solution, and regulating the pH value of the yttrium chloride solution until white precipitates just appear; adding the yttrium chloride solution into an ammonium hydrogen carbonate solution containing a dispersing agent drop